IMPLEMENTATION OF CHARACTER EDUCATION VALUES IN ISLAMIC BOARDING SCHOOLS (A CASE STUDY OF MA NU DARUL ISLAH SURENGEDE, WONOSOBO) - anif adniyansah; Maryono; Fatiatun (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This study explores the implementation of character education values in Islamic boarding schools, with a case study at MA NU Darul Islah Surengede, Wonosobo. Employing a descriptive qualitative approach through interviews, observation, and document analysis, the research examines how pesantren-based character values are integrated into the educational process. The findings reveal that character education at MA NU Darul Islah is implemented through a holistic approach that combines the national Merdeka Curriculum with the distinctive Nahdlatul Ulama pesantren curriculum via the Madrasah Operational Curriculum (KOM). Key values cultivated include religiosity/spirituality, noble character (akhlaq), discipline, responsibility, independence, religious moderation, social concern, and leadership. These values are instilled through daily habituation programs (such as congregational prayers, Qur’an recitation, mujahadah, and classroom cleaning schedules), teacher role modeling, and extracurricular activities. Supporting factors include visionary leadership, consistent teacher role modeling, strong stakeholder collaboration, and the supportive pesantren environment. However, challenges persist, including students’ diverse backgrounds, the dominance of academic focus, uncontrolled use of mobile phones, and external environmental influences. The study concludes that effective character education in pesantren requires consistent integration of formal and non-formal approaches, strong role modeling by educators, and continuous collaboration among all stakeholders to overcome existing obstacles.